2011
DOI: 10.1155/2011/536062
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytosis: Diagnostic Evaluation, Thrombotic Risk Stratification, and Risk-Based Management Strategies

Abstract: Thrombocytosis is a commonly encountered clinical scenario, with a large proportion of cases discovered incidentally. The differential diagnosis for thrombocytosis is broad and the diagnostic process can be challenging. Thrombocytosis can be spurious, attributed to a reactive process or due to clonal disorder. This distinction is important as it carries implications for evaluation, prognosis, and treatment. Clonal thrombocytosis associated with the myeloproliferative neoplasms, especially essential thrombocyth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
108
1
13

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(125 citation statements)
references
References 169 publications
(216 reference statements)
3
108
1
13
Order By: Relevance
“…An increased risk of vascular complications over time is the main clinical feature of ET; consequently, the evaluation of the thrombotic risk at diagnosis is the crucial point for treatment decision [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…An increased risk of vascular complications over time is the main clinical feature of ET; consequently, the evaluation of the thrombotic risk at diagnosis is the crucial point for treatment decision [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The main causes of death are thrombotic events and evolution into myelofibrotic phase or secondary myelodisplasia/acute leukemia [3]; furthermore, the most frequent complications occurring in ET patients are either arterial or venous thromboses [4]. The treatment of ET patients with cytoreductive drugs is effective in reducing the incidence of these thrombotic events [5] but could be associated with an higher rate of leukemic evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated values are also seen among patients suffering from polycythemia, chronic myeloid leukemia, acute infections and chronic inflammatory conditions [1].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown a risk as low as 1.6% for a thromboembolic complication of reactive thrombocytosis. This is why it is generally not recommended to treat with aspirin for prophylactic purposes in patients with reactive thrombocytosis [1].…”
Section: Discussionmentioning
confidence: 99%